Randomized clinical controlled trial on the effectiveness of conventional and orthodontic manual toothbrushes - Lisiane Krieger Gomes; Carlos Frederico Sarmento; Flávio Roberto Guerra Seabra; Patrícia Bittencourt Dutra dos Santos; Fábio Henrique de Sa Leitão Pinheiro (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The objective of this study was to compare the effectiveness of two manual toothbrushes (conventional and orthodontic). The following clinical parameters were used: VPI (visible plaque index) and GBI (gingival bleeding index). Patients, 64 total (30 males and 34 females), in the permanent dentition, with a mean age of 17.8 years, were randomly selected from a practice specializing in orthodontics. Each participant received audio-visual instructions on oral hygiene as well as a kit of materials containing two manual toothbrushes (orthodontic and conventional). Each toothbrush was randomly allocated to one side of the mouth (split-mouth design) and used for a period of approximately 4 weeks. The VPI and GBI were measured by a single calibrated examiner before (T0) and after (T1) the implementation of interventions. The Mann-Whitney test was used to compare the VPI values between the groups, and the Student t-test for independent samples was used to compare GBI values. The level of significance was set at 5%. No statistically significant difference was observed between the groups at T0 for both VPI and GBI, and at T1 for the GBI. The manual orthodontic toothbrush produced a statistically lower VPI (P < 0.05) at T1, but this did not seem to be of clinical importance.